Analysis of the Implementation of Tourism Education and Animal Welfare on the Formation of the Premium Cikole Civet Coffee Brand Image: Analisis Implementasi Edukasi Pariwisata dan Kesejahteraan Hewan (Animal Welfare) terhadap Pembentukan Citra Merek Premium Kopi Luwak Cikole - Muhammad Rizki Akbar Al Afif; Dhioktafian Binawan Putra; Tegar Bahrul Nasrulloh; Akhmad Alfandi Ardhiansyah (Universitas Muhammadiyah Sidoarjo, 2026)
General Background The global civet coffee industry faces severe reputational risks due to animal exploitation concerns in commercial captivity. Specific Background Kopi Luwak Cikole in Lembang applies ethical agrotourism integrating interpretive communication education and animal welfare principles to differentiate its market position. Knowledge Gap Empirical studies explicitly linking visitor interpretive education and observable animal welfare standards with premium brand image formation remain scarce. Aims This study analyzes how tourism education and animal welfare practices synergistically contribute to building a premium brand image. Results Findings show interpretive communication shifts visitor perception from initial skepticism to value justification, while transparent Five Freedoms implementation provides ethical trust that legitimizes premium pricing. Novelty This research reveals a sequential synergistic mechanism where cognitive educational alignment and ethical legitimation jointly construct competitive brand equity. Implications Agritourism managers can utilize transparent animal welfare and structured interpretation to counter negative industry narratives and establish sustainable premium brand positioning. Key Findings Highlights Interpretive communication successfully shifts visitor perceptions to justify premium pricing for ethical civet coffee. Transparent implementation of the Five Freedoms builds ethical trust and mitigates global industry exploitation criticisms. Synergistic interaction between visitor education and animal welfare practices constructs a unique, hard-to-replicate brand image. Keywords: Tourism Education, Animal Welfare, Premium Brand Image, Civet Coffee, Ethical Agrotourism